2021
DOI: 10.1101/2021.01.10.426133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Flowering Time RegulatorFLKControls Pathogen Defense inArabidopsis thaliana

Abstract: Plant disease resistance is a complex process that is maintained in an intricate balance with development. Increasing evidence indicates the importance of post-transcriptional regulation of plant defense by RNA binding proteins. The K homology (KH) repeat is an ancient RNA binding motif found in proteins from diverse organisms. The role of KH domain proteins in pathogen resistance is not well known. From a genetic screen aimed to uncover novel defense genes in Arabidopsis, we identified a new allele of the can… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…S11 ), several closely related family members of this RNA binding protein in Arabidopsis are known to regulate flowering time ( 60 ), suggesting an off-target action of the effector. In this regard, it is interesting to note that whereas KRBP1 acts as a susceptibility factor ( 33 ), its closely related homolog FLK is a positive regulator of flowering ( 61 ), and a recent preliminary report suggests that it is also a positive regulator of plant immunity ( 62 ). It will be interesting to see whether Pi04089 interacts with a closely related K homology (KH) RNA binding protein, such as FLK.…”
Section: Discussionmentioning
confidence: 99%
“…S11 ), several closely related family members of this RNA binding protein in Arabidopsis are known to regulate flowering time ( 60 ), suggesting an off-target action of the effector. In this regard, it is interesting to note that whereas KRBP1 acts as a susceptibility factor ( 33 ), its closely related homolog FLK is a positive regulator of flowering ( 61 ), and a recent preliminary report suggests that it is also a positive regulator of plant immunity ( 62 ). It will be interesting to see whether Pi04089 interacts with a closely related K homology (KH) RNA binding protein, such as FLK.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of plant immunity leads to a series of reactions, including an increase in reactive oxygen species (ROS), Ca 2+ influx, mitogen‐activated protein kinase activation, and regional cell death (Boller & Felix, 2009 ; Cheng et al, 2019 ; Spoel & Dong, 2012 ; Zipfel & Oldroyd, 2017 ). Numerous proteins, such as the transcription factor BZR1, which is involved in brassinosteroid signalling (Qi et al, 2021 ), mitogen‐activated protein kinase kinases (Rufian et al, 2021 ), and FLOWERING LOCUS KH domain (FLK) (Fabian et al, 2021 ), have been reported to regulate plant immune responses. Among these, FLK is an RNA‐binding protein (RBP) that regulates plant development (Lim et al, 2004 ), the ROS‐scavenging enzyme catalase, and plant immunity (Fabian et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous proteins, such as the transcription factor BZR1, which is involved in brassinosteroid signalling (Qi et al, 2021 ), mitogen‐activated protein kinase kinases (Rufian et al, 2021 ), and FLOWERING LOCUS KH domain (FLK) (Fabian et al, 2021 ), have been reported to regulate plant immune responses. Among these, FLK is an RNA‐binding protein (RBP) that regulates plant development (Lim et al, 2004 ), the ROS‐scavenging enzyme catalase, and plant immunity (Fabian et al, 2021 ). Therefore, we aimed to investigate the role of RBPs in pathogen defence and ROS regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation